2019
DOI: 10.3846/btp.2019.02
|View full text |Cite
|
Sign up to set email alerts
|

Sharia mutual funds performance in Indonesia

Abstract: The study aims to measure each Sharia mutual fund performance and compare with market performance in Indonesia. Sharia mutual fund investment instruments in Indonesia have positive developments over the period from 2012 to 2017. These positive developments add to the option of investment instruments for public, especially investors who put forward the principles of Sharia. This research was conducted so that the public could have scientific information about Sharia mutual funds that have the best performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…However, they declared that these strategies need further verification. Robiyanto et al (2019) used the Sharpe, Treynor, and Jensen measures to assess the performance of 21 Indonesian mutual funds from 2012-2017, and the findings are consistent with those of Arif et al (2019).…”
Section: Introductionsupporting
confidence: 73%
“…However, they declared that these strategies need further verification. Robiyanto et al (2019) used the Sharpe, Treynor, and Jensen measures to assess the performance of 21 Indonesian mutual funds from 2012-2017, and the findings are consistent with those of Arif et al (2019).…”
Section: Introductionsupporting
confidence: 73%
“…Endogenous variable in this study is mutual funds performance by sharpe ratio measured by the sum of mutual funds's return and market return divided by standart deviation. The performance measurement method applied used measured the performance with the Sharpe methods (Pangestuti et al 2017;Robiyanto et al 2019). The Sharpe Index value is used as a proxy for mutual funds performance because it considers systematic and unsystematic risk.…”
Section: Data Description and Methodologymentioning
confidence: 99%
“…Its main characteristic is that this model assumes that there is only one factor that influences the return of securities. The methodology most frequently used in estimating market beta is to do time series regression, and then perform cross-sectional regression between the average profit rate and beta estimated from the time series regression (Robiyanto, Santoso, & Ernayani, 2019). Lintner (1965) used the same method employed by Sharpe (1964) plus the use of unsystematic risk variables (represented by the variance of residual terms) and found that the value of the intercept was too high and the residual terms were included in the pricing.…”
Section: Multi-index Modelmentioning
confidence: 99%